Narrative elements in the novel "Utopia" by Ahmed Khaled Tawfiq - فارساني , عباس یداللهي; زاده, جواد سعدون; حسیني, زهراء سیّاحي (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
This research aims according to the descriptive, analytical, and statistical method of the narrative elements found in the Utopia novel. Through these elements, he seeks to explain what the Egyptian writer Ahmed Khaled Tawfiq did. From his presentation of the ideas and social issues that swept his society. The writer relied on building parts of his novel on narrative elements, such as (primary, secondary, marginal characters). Which constitutes the important element in serving the writer's goals in explaining poverty, injustice, and class differentiation. Use the dialogue technique (external and internal), whose presence was the highest among the other elements. For the consistency of events, he benefited from the plot (beginning, conflict, anxiety, climax, and end), and he arranged and developed it perfectly. As they are related to each other, and also benefited from narration, description, time and placeAnd he made its description very close to reality, expressing the struggle between classes, and exposing the falsity of the rulers and officials in Egyptian society. And he was creative in narrating the narration, so he moved from the external narration and description to the inner reality of the human being with honesty and boldness.